Perancangan Pengalaman Pengguna Aplikasi Pemantauan Kegiatan Masjid berbasis Piranti Bergerak menggunakan Human-Centered Design (Kasus: Masjid Ibnu Sina Jl. Veteran, Malang) - Iqbal Putra Santosa; Ismiarta Aknuranda; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Ibnu Sina Mosque is one of the large mosques in Malang City which has various agendas of activities carried out in serving its congregation. In every activity the mosque administrators always coordinate routinely regarding the work given. Currently, the coordination and monitoring of the work carried out by mosque administrators is still through the WhatsApp messaging application. This raises several problems, such as the information related to the progress of the work submitted so that it collides with other information so that the person in charge of the work and the head of takmir as the highest person in charge of managing the mosque find it difficult to monitoring these jobs. Based on these problems, the user experience of the mosque activity monitoring application will be designed. So with this design, it is hoped that the work supervision process will be easier, more effective and efficient. The design process uses a Human-Centered Design approach which is iterative and involves users at every stage. The first stages begins with determining the context of use, determining user needs, making design solutions, evaluating design solutions and improving design solutions. Evaluation using usability testing method to six participants. The results of the evaluation on the aspect of effectiveness produce a success rate of 100%. Efficiency is calculated using time-based efficiency to produce a score of 0.024 goals/sec for the participating members, and 0.056 goals/sec for the head of takmir participants. The aspect of satisfaction was measured using a single ease question, getting a score of 6.2 for members and 6.17 for the head of takmir. The results of evaluation also found 13 problems that will be improved on the design solution.